Research on the Physico-Chemical Properties of Soils Locality Dobrosloveni, Olt County for Sustainable Agriculture - Stănilă, Anca-Luiza (Journal of Applied Biotechnology, 2021)
The studied territory located in the central-western part of Olt County, belongs to the Caracal Plain and extremely little in the Leu-Rotunda Field in the SW part, both as divisions of the Romanati Plain. Locality presents a predominant relief of plain low altitude that is characterized by alluvio-proluvial plains moderately fragmented with local terraces, covered with loess-like deposit but relief of saucer. The soil cover of the territory under study is the direct reflection of all environmental factors, each having a role in the pedogenetic processes. Climate, as a pedogenetic factor, acted by its components, namely: temperature, precipitation, evapotranspiration, global radiation. Forest steppe vegetation was the supply of organic matter and biomass, because the hydrological regime is deficient, but especially the lithological substrate (loess-like complex) to steer solification to types characteristic of the cernisols class. Under the influence of environmental factors and pedogenetic processes within the locality Dobrosloveni it formed a wide range of soils, namely: protisols, cernisols, luvisols and hydrisols.